Teaching digital literature in secondary school: multimodal meaning-making and students’ interpretive engagement - Dewi Masyithoh (Lingua Technica: Journal of Digital Literary Studies, 2025)
Background: The growing use of digital platforms in secondary education has changed how literature is accessed, discussed, and produced, yet many classroom practices still treat technology mainly as a tool for distributing materials rather than as part of literary meaning-making. Objective: This study aims to examine how digital literature is taught in one public senior high school in East Java. Method: Using a qualitative case study design, this research analysed lesson documents, teaching materials, selected digital literary texts, classroom observations, platform interactions, student reflections, creative products, teacher interviews, selected student interviews, and assessment artefacts through TPACK Analysis, Multimodal Discourse Analysis, and Reader-Response Analysis. Results: The findings show that technology integration was uneven: Google Classroom, Padlet, Canva, mobile phones, online texts, and projection media supported access, discussion, reflection, and production, but lesson objectives and assessment rubrics still relied heavily on print-based literary categories. Digital literary texts expanded meaning-making through verbal, visual, auditory, spatial, kinetic, interactive, and platform-based modes. Implication: Students demonstrated strong affective, social, and creative engagement, especially through digital poems, visual stories, posters, and video responses, but they experienced difficulty with hyperlinks, non-linear narration, interface structures, and multimodal coherence. Novelty: The novelty of this study lies in proposing a corpus-based classroom framework that connects TPACK, multimodal discourse, and reader-response perspectives to examine digital literature as instructional design, textual form, and student reading experience.